Penerapan Pemberian Punishment dan Reward pada Pembelajaran Fiqih di SMP Swasta Darul Ulum Aceh Tenggara - Gusti Randa Ras; Mavianti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is motivated by the implementation of punishment and reward at the Darul Ulum Private Middle School in Southeast Aceh. The majority of students have difficulty academically and are less enthusiastic about studying fiqh. As a result, the author is curious about how children at the Darul Ulum Private Middle School in Southeast Aceh receive rewards and punishment during the learning process. This type of research is field research with a descriptive qualitative method that describes the application of punishment and rewards in fiqh subjects at Darul Ulum Private Middle School, Southeast Aceh. In collecting data, researchers used observation and interview techniques. The main data sources and informants in this research were fiqh teachers and their supporting informants, several students. Meanwhile, to analyze it, researchers used data reduction steps, data presentation, and drawing conclusions. The results of the research stated that at Darul Ulum Private Middle School in Southeast Aceh, rewards and punishment were given with the aim of improving students' welfare and arousing interest in learning so that they felt satisfied and more enthusiastic about learning. Punishment is also intended to educate and improve student performance in the future. Punishment and rewards applied by teachers also take various forms, including rewards in the form of praise, additional grades, gifts and punishment, some in the form of preventive and repressive. The implementation of punishment and rewards that have been implemented by fiqh teachers at Darul Ulum Private Middle School, Southeast Aceh. Students can move in a more positive direction because of several existing approaches and forms regarding behavior.